Promotion, prevention and early intervention for mental health : a monograph, 2000 - National Mental Health Strategy .; Australia. Department of Health and Aged Care. Mental Health and Special Programs Branch; National Public Health Partnership (Australia); Australian Health Ministers' Advisory Council. National Mental Health Working Group (Canberra : Mental Health and Special Programs Branch, Commonwealth Department of Health and Aged Care, 2000)
Promotion, prevention and early intervention for mental health: a monograph, 2000
1. Introduction -- 2. The influences on mental health -- 3. Conceptual framework for promotion, prevention and early intervention activities -- 4. Promotion, prevention and early intervention for mental health -- 5. A whole-of-lifespan approach to mental health and mental illness -- 6. Special population groups -- 7. Disorder-specific issues -- 8. Towards good practice in promotion, prevention and early intervention.
"National mental health strategy" -- Cover.
"This Monograph 2000 is a companion document to the National Action Plan for Promotion, Prevention and Early Intervention for Mental Health (Action Plan 2000)" -- p. iii.
Bibliography: p. 134-162.
Keywords: National Mental Health Strategy (Australia); Mental health -- Australia; Mental health; Mental illness -- Australia -- Prevention; Health planning -- Australia; Health policy -- Australia; Mental health